2021
DOI: 10.1155/2021/3740476
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Big Data Resource Management: Using Smart Grid Systems as a Case Study

Abstract: Big data has recently been a prominent topic of research due to the exponential growth of data every year. This massive growth of data is causing problems with resource management. The available literature does not address this problem in depth. Therefore, in this article, we aim to cover the topic of resource management for big data in detail. We addressed resource management from the perspective of smart grids for a better understanding. This study includes a number of tools and methods, such as Hadoop and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…1 is depicted to represent the relations among stages of the big data value chain, characteristics of big data, and stage-related popular technologies and tools. Moreover, to the best of my knowledge, characteristics of big data are generally represented standalone in big data research [40][34] [41]. However, in Fig.…”
Section: Big Data Value Chain Modelmentioning
confidence: 99%
“…1 is depicted to represent the relations among stages of the big data value chain, characteristics of big data, and stage-related popular technologies and tools. Moreover, to the best of my knowledge, characteristics of big data are generally represented standalone in big data research [40][34] [41]. However, in Fig.…”
Section: Big Data Value Chain Modelmentioning
confidence: 99%
“…With the popularization and application of the concept of the smart grid, the danger of the data silo issue in the smart grid has become more and more prominent, and an effective way to solve this issue is to establish a reasonable and effective data-sharing model [1]. In today's society, with the rapid development of science and technology, the interconnection of data has become an important measure with which to enhance scientific and technological innovation in all walks of life and even the country, and many studies have shown that the interoperability and sharing of data can improve the utilization rate of data resources [2][3][4][5], accelerate the dissemination of data resources, and provide a very convenient way for people's work, life, and travel. However, in the process of data sharing, users' unwillingness to share data is affected by the formation of a mutual trust relationship and economic utility.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of affordable technology, widespread use of the internet, and the development of smart and portable devices that can connect to the internet via wireless or cellular networks, as well as the increasing number of different sectors and individuals utilizing these technologies, have significantly increased the amount of data generated in various sizes, formats, speeds, and types (Khan et al, 2021). Moreover, this digital transformation has triggered the generation of data and profoundly altered people's daily activities and habits as a result of the implementation of various applications in education, finance, health care, business, commerce, manufacturing, retail, and government services to facilitate daily activities (Dutta & Jayapal, 2016;Kejariwal et al, 2017;Syed et al, 2021;Tang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%